Methodological alternative for the physical diagnosis of the blind schoolchild from the context of Physical Education - Alberto Bautista Sánchez Oms; Elizabeth González Nocedo (Podium, 2020)
Studies are limited in terms of assessing the physical component at early ages of development and focusing on blindness. Most of the studies related to blindness were carried out in order to contribute to the development of motor skills and not to the study of the physical component. Therefore, the research evolved from a current physical diagnosis of the blind student, the selection of methods and functional tests with their adaptations, as well as the assessment of the viability of their application in special education. It was found that the comprehensive pedagogical diagnosis has limitations, since it does not include aspects of the physical component, which hinders the adequate direction of the pedagogical process of Special Physical Education. In this study, methods from both the empirical and theoretical levels were used, with the case studies being of great significance. In general, it has been observed that the Centos de Diagnóstico y Orientación do not apply tests to evaluate the physical component of blind schoolchildren, which affects the quality of the physical education teaching process.